2014
DOI: 10.1186/cc13942
|View full text |Cite
|
Sign up to set email alerts
|

High dose of tigecycline for extremely resistant Gram-negative pneumonia: yes, we can

Abstract: Few antimicrobials are currently active to treat infections caused by extremely resistant Gram-negative bacilli (ERGNB), which represent a serious global public health concern. Tigecycline, which covers the majority of these ERGNB (with the exception of Pseudomonas aeruginosa), is not currently approved for hospital-acquired pneumonia, and several meta-analyses have suggested an increased risk of death in patients receiving this antibiotic. Other studies suggest that the use of high-dose tigecycline may repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Potential prognostic factors for 28-day mortality were evaluated by means of univariate analysis (Annex 3). The logistics regression analysis showed that patients with septic shock (OR = 0.33, 95% CI, 0.12–0.92), MODS (OR = 0.26, 95% CI, 0.08–0.83), and higher APACHE II score (OR = 0.89, 95% CI, 0.80–0.98) were of high risk in mortality, which is consistent with related report that the HD of TGC did not increase clinical mortality [ 17 ] (Table 7 ).…”
Section: Resultssupporting
confidence: 89%
“…Potential prognostic factors for 28-day mortality were evaluated by means of univariate analysis (Annex 3). The logistics regression analysis showed that patients with septic shock (OR = 0.33, 95% CI, 0.12–0.92), MODS (OR = 0.26, 95% CI, 0.08–0.83), and higher APACHE II score (OR = 0.89, 95% CI, 0.80–0.98) were of high risk in mortality, which is consistent with related report that the HD of TGC did not increase clinical mortality [ 17 ] (Table 7 ).…”
Section: Resultssupporting
confidence: 89%
“… 19 Five studies did not report a difference in eosinophil count between infectious and non-infectious SIRS groups. 22 , 23 , 33 35 Nevertheless, these studies are limited by small sample sizes (range 66–185) and cross-sectional study designs.…”
Section: Resultsmentioning
confidence: 99%
“…We read with interest the paper by De Pascale and colleagues [ 1 ] and the accompanying editorial [ 2 ] on high-dose tigecycline (TGC) in critically ill patients with severe infections due to multidrug-resistant bacteria. We agree that the currently recommended TGC dose (100 mg loading followed by 50 mg twice daily) may be largely insufficient for treatment of such infections and may promote resistance.…”
mentioning
confidence: 99%